Effectiveness of Watching Movie of Students’ Speaking Ability at the Twelfth Grade of MAN Singkil - Hajiati Manik; Salamuddin (Education & Learning, 2023)
The research is aimed to find out the effectiveness of watching movie of students’ speaking ability at the twelfth grade of MAN Singkil. The subject of this research was aclass XII IPA 1 as an experimental class and class XII IPA 2 as a control class. This thesis applied Experimental research. The research instrument is the speaking test in the form of a pre-test and post-test. The data analyzed by T-test. To analyze the data, the researcher determined the scoring classification which includes pronunciation, grammatical, vocabulary, fluency and comprehension. The population of the research was the twelfth-grade students of MAN Singkil. The sample was class XII IPA 1 and XII IPA 2 the total of samples is 58 students. The results of this study indicate that there is a significant influence from the use of watching movie media. This can be seen from the defference in the average scores of students from the pre-test and post-test in the experimental class which increased from 62 to 89. The average post-test score in the control class was 53 while the post-test score in the experimental class was 89 is higher than the average value of the control class. This means that watching movie media can be applied to improve students’ speaking ability.